A web-based and mobile randomised controlled trial providing complementary feeding guidelines to first-time parents in France to promote responsive parental feeding practices, healthy children's eating behaviour and optimal body mass index: the NutrienT trial study protocol - Camille Riera-Navarro; Camille Schwartz; Pauline Ducrot; Laurence Noirot; Corinne Delamaire; Edith Sales-Wuillemin; Denis S. Semama; Sandrine Lioret; Sophie Nicklaus (BMC, 2024)
Abstract Background Childhood obesity is a crucial public health issue. Early childhood is a critical time to foster the establishment of healthy eating behaviours and growth, which are partly shaped by parental feeding practices. To inform French parents of the recently updated national complementary feeding guidelines for 0-3 years (in terms of nutrition and responsive feeding as a mean to encourage infant appetite control skills and promote healthy growth), an official printed brochure was developed and nationally disseminated in 2021 by the French public health agency, Santé publique France. This randomised controlled trial aims to investigate whether the provision of guidelines through digital (smartphone application) and printed (brochure) tools (vs. the printed brochure alone, usual service) results in healthier parental feeding practices, infant eating behaviours and weight status. Methods This double-blinded monocentric 2-arm trial is currently conducted among first-time parents living in the area of Dijon (France) and recruited in a maternity ward. From child age 3 to 36 months (mo), an app provides a range of 106 age-adapted messages, including dietary recommendations, educational advice, recipes, and tips (intervention group only). Additionally, parents of both groups are provided with 48 messages related to child general development and the printed brochure at child age 2.7 mo. The primary outcome is the body mass index (BMI) z-score at child age 36 mo. Secondary outcome measures include a combination of online parents' reports and behavioural assessments (experimental meals) of parental feeding practices and infant eating behaviours from inclusion to 36 months of age. Analyses of covariance on these outcomes will assess the effect of the intervention, adjusted for relevant confounders. Complementary mediation and moderation analyses will be conducted. Sample size was determined to be n = 118 in each arm of the trial, plus 20% to compensate for potential attrition. Discussion This is the first public eHealth randomised control trial in France to assess the effect of a web-based and mobile intervention targeted to first-time parents to improve child feeding practices and child growth. Trial registration This trial was registered at clinicaltrials.gov as NCT05285761 (March 18, 2022).